Strategies for comprehending and integrating texts and videos. (October 2018) - List, Alexandra
Abstract: This study examines students' strategic processing when participants were asked to comprehend and integrate information presented via two texts or two videos. Evidence was found for strategies being both consistent (e.g., connecting content with prior knowledge) and distinct (e.g., vocabulary) across modalities of information presentation. No differences in comprehension and integration performance were identified across conditions, a variety of strategies (e.g., directing attention, connecting with prior knowledge) were associated with measures of both comprehension and integration. As this is among the first studies to compare strategies supporting video versus text integration, directions for future research are discussed. Highlights: Strategies for comprehending and integrating texts and videos were identified. Important differences in patterns of strategy use were found across conditions. A variety of strategies predicted students' comprehension scores across modalities. A variety of strategies predicted students' integration scores across modalities.